IMPLEMENTASI IMPLEMENTASI METODOLOGI EXTREME PROGRAMMING PADA APLIKASI SISTEM INFORMASI REKAM MEDIS STUDI KASUS KLINIK GAGA MEDIKA DI KALIDERES EXTREME PROGRAMMING PADA APLIKASI SISTEM INFORMASI REKAM MEDIS STUDI KASUS KLINIK GAGA MEDIKA DI KALIDERES - Dea Silpidia Dahtyar; Yudi Kurniawan (CV. Multi Kreasi Media, 2024)
Along with the development of information technology, the need for fast, accurate and relevant information is increasing. Accurate information is needed in everyday life. Gaga Medika Clinic strives to provide the best service to its patients. In its activities, the processes carried out still use a form of paper-based medical record service or so-called paper-based document, namely, by using a master book for recording and archiving it. This method is very ineffective, and besides that, storing document archives manually can slow down data retrieval. Patient visit reports and patient disease report data also still use manual recording using a notebook, and it is feared that it can be easily damaged or easily lost. Therefore, the authors want to create an application that can help overcome existing problems, such as medical record information systems. This application is made using the PHP programming language and uses the MySQL database program to create the database. The results of this study with the existence of a medical record information system at the Gaga Medika clinic help the clinic not lose data if there are patients who have not visited the Gaga Medika clinic for a long time.